Determinants of Undetected Hypertension among Women Aged 15-49 Years in India with Special Reference to Use of Smokeless Tobacco - Vijit Deepani; Lucky Singh; Nongzaimayum Tawfeeq Alee; Senthanro Ovung; Saritha Nair (Wolters Kluwer Medknow Publications, 2024)
Background: Hypertension significantly contributes to avoidable morbidity and mortality. The literature indicates an increased risk of hypertension among tobacco users. This study examines the determinants of undetected hypertension among women in India and infers its relationship with smokeless tobacco (SLT) use. Materials and Methods: A nationally representative sample of 699,686 women (aged 15-49 years) in the National Family Health Survey-4 (2015-2016) was utilized. Women participants who did not self-report hypertension but their mean blood pressure measured during the interview were above 140/90 mmHg were considered as having undetected hypertension. Multivariate logistic regression was used to examine the association between hypertension and predictor variables including the use of SLT. Results: The prevalence of undetected hypertension was found to be 9.1% among women in India, and in comparison to non-SLT users, a higher prevalence of hypertension was observed among current SLT users. Age, illiteracy, obesity, use of SLT, alcohol consumption, and residing in Northeast India were found to be significant determinants of hypertension. Conclusion: Preventing the use of SLT through socioculturally tailored tobacco control interventions, raising awareness for behavior and lifestyle changes, and regular screening for hypertension in communities may have the potential to reduce the increasing burden of hypertension among women in India.